Religiosity and Environmental Care Attitudes: A Correlational Study Among Islamic Elementary School Students in Bayat District - Alif Faizah; Dita Purwinda Anggrella (JENIUS (Journal of Education Policy and Elementary Education Issues), 2026)
This study was motivated by the suboptimal level of environmental care among fifth-grade students in Islamic elementary schools (Madrasah Ibtidaiyah) across Bayat District. The study was grounded in the Value–Belief–Norm (VBN) Theory, which explains that individuals' values and beliefs influence their pro-environmental behavior. The objective of this study was to examine the relationship between religiosity and environmental care attitudes among fifth-grade students in Madrasah Ibtidaiyah throughout Bayat District. A quantitative approach with a correlational research design was employed. The population consisted of 108 students, from which a sample of 86 students was selected using the Slovin formula and proportional random sampling. Empirical validity testing indicated that 21 of the 22 religiosity questionnaire items and 26 of the 30 environmental care attitude questionnaire items were valid. Reliability testing yielded Cronbach's alpha coefficients of 0.807 for the religiosity scale and 0.847 for the environmental care attitude scale, indicating good internal consistency. The correlation analysis (r = .767, p < .001) revealed a strong, positive, and statistically significant relationship between religiosity and environmental care attitudes. Furthermore, the coefficient of determination (R² = .588) indicated that approximately 58.8% of the variance in students' environmental care attitudes was associated with religiosity, while the remaining 41.2% was explained by other factors. These findings highlight the importance of integrating environmental care into Islamic education and daily religious practices, enabling students not only to strengthen their religious commitment but also to develop greater responsibility toward environmental sustainability.